RELASIONAL BERPIKIR DENGAN BAHASA - Junifer Siregar (Universitas Negeri Medan, 2014)
This study wants to describe the relationship between the languages and mind in early childhood and want to describe the role of parents, teachers, and the environment indeveloping language skills and thinking in early childhood. From the corner of thepsychology of early childhood development is a child who has limitations in the ability tothink and speak. At this stage the child's way of thinking, among others, still egocentric.Therefore that an increase in the child's thinking, activities intended to enable them to perform classification, logical thinking, and trained to solve problem.They should also bestimulated to learn about a variety of concepts such as the concept of space, the concept oftime, and the concept of number. This research was conducted by using a qualitative description.Activities that can stimulate a child's ability to think is to improve children's language abilities. The language used by the teacher is a language that raw organized yet simple and communicative. But in early childhood development to date is not known precisely themechanism of how a child learns a language so that the language can be learned.Based on the above, the authors are interested in doing research for